{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Section 3.9-solutions

# Section 3.9-solutions - = 8 x sec 2(4 x 2 Consequently dy =...

This preview shows pages 1–2. Sign up to view the full content.

to (aqt73) – Section 3.9 – isaacson – (55826) 1 This print-out should have 3 questions. Multiple-choice questions may continue on the next column or page – fnd all choices beFore answering. 001 10.0 points ±ind the linearization oF f ( x ) = 1 6 + x at x = 0. 1. L ( x ) = 1 6 p 1 + 1 12 x P 2. L ( x ) = 1 6 + 1 6 x 3. L ( x ) = 1 6 p 1 + 1 12 x P 4. L ( x ) = 1 6 - 1 6 x 5. L ( x ) = 1 6 p 1 - 1 6 x P 6. L ( x ) = 1 6 p 1 - 1 12 x P correct Explanation: The linearization oF f is the Function L ( x ) = f (0) + f (0) x . But For the Function f ( x ) = 1 6 + x = (6 + x ) 1 / 2 , the Chain Rule ensures that f ( x ) = - 1 2 (6 + x ) 3 / 2 . Consequently, f (0) = 1 6 , f (0) = - 1 12 6 , and so L ( x ) = 1 6 p 1 - 1 12 x P . 002 10.0 points ±ind the di²erential, dy , oF y = f ( x ) = tan(4 x 2 ) . 1. dy = 4 sec 2 (4 x 2 ) tan(4 x 2 ) + dx 2. dy = 4 sec 2 (4 x 2 ) tan(4 x 2 ) 3. dy = 4 sec 2 (4 x 2 ) tan(4 x 2 ) dx 4. dy = 8 x sec 2 (4 x 2 ) 5. dy = 8 x sec 2 (4 x ) + dx 6. dy = 8 x sec 2 (4 x 2 ) dx correct Explanation: The di²erential, dy , oF y = f ( x ) is given by dy = f ( x ) dx . On the other hand, d dx tan x = sec 2 x . Thus by the Chain Rule, f ( x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ) = 8 x sec 2 (4 x 2 ) . Consequently, dy = 8 x sec 2 (4 x 2 ) dx . keywords: di²erential, trig Function, tan Func-tion, Chain Rule, 003 10.0 points to (aqt73) – Section 3.9 – isaacson – (55826) 2 Find the diferential dy when y = 1 + sin x 3-sin x . 1. dy = 3 sin x (3-sin x ) 2 dx 2. dy =-cos x 3-sin x dx 3. dy = sin x (3-sin x ) 2 dx 4. dy =-4 cos x 3-sin x dx 5. dy = 4 cos x (3-sin x ) 2 dx correct 6. dy =-4 cos x (3-sin x ) 2 dx Explanation: A±ter diferentiation o± y = 1 + sin x 3-sin x using the quotient rule we see that dy = (3-sin x ) cos x + cos x (1 + sin x ) (3-sin x ) 2 dx . Consequently, dy = 4 cos x (3-sin x ) 2 dx ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

Section 3.9-solutions - = 8 x sec 2(4 x 2 Consequently dy =...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online